Marketing performance of small and medium industrial shoe entrepreneurs in greater Bandung - Keni Kaniawati; Andhi Sukma; Desi Oktaviani (Institute of Computer Science (IOCS), 2024)
This study aims to analyze and design SIDATA, a database management system tailored for final project data, utilizing the Rapid Application Development (RAD) methodology. The primary objective is to enhance the efficiency and responsiveness of SIDATA in managing, storing, and retrieving final project-related information within an academic setting. The research employs a systematic approach that involves an initial analysis of user requirements and a comprehensive understanding of the final project data attributes. The RAD methodology is then applied, focusing on iterative development, quick prototyping, and continuous user feedback to tailor SIDATA to the specific needs of its users. The methodology allows for swift adjustments and refinements throughout the development process. Implementing RAD in the analysis and design of SIDATA has led to a more user-centric and adaptive database management system. SIDATA now efficiently captures, organizes, and presents final project data, streamlining the process for students, faculty, and administrators. The iterative nature of RAD facilitated the rapid development of features and ensured that SIDATA remained aligned with the evolving requirements of the academic environment. In conclusion, applying RAD in the analysis and design of SIDATA has proven to be instrumental in creating a responsive, user-friendly database management system. The iterative and collaborative nature of RAD has enhanced the adaptability of SIDATA to the dynamic needs of its users, providing an efficient platform for managing final project data within an academic context